Evaluation of children with solid thyroid nodules: a single-center experience - Gunbey, Omer; Paksoy, Firdevs Dilara; Yildirim Acar, Nurdan; Okdemir, Deniz; Esen, Ihsan (Walter de Gruyter Gmbh, 2026)
Objectives This study aimed to evaluate the cytopathological and histopathological features of solid thyroid nodules detected in the pediatric population and to investigate the diagnostic value of thyroid ultrasonography (US) findings.Methods A retrospective review was conducted on 53 pediatric and adolescent patients who were followed up for solid thyroid nodules and underwent thyroid biopsy at a university hospital between January 2020 and December 2025. Data on patients were collected. Biopsy results were classified according to the Bethesda system. Ultrasonographic features considered suggestive of malignancy were noted.Results The median age of the patients included in the study was 16.1 years (range: 5.5-18.0), and 81.1 % were female. The most common cytopathological Bethesda categories were: category 2 (benign) in 47.2 % of cases, category 1 (nondiagnostic) in 24.5 %, category 3 (atypia of undetermined significance) in 18.9 %, category 5 (suspicious for malignancy) in 7.5 %, and category 6 (malignant) in 1.9 %. Among 19 patients who underwent surgery, 12 (63.2 %) were diagnosed with papillary thyroid carcinoma (PTC). In most of these PTC cases, three or more ultrasonographic malignancy criteria were present. However, PTC was also detected in two patients who had been cytopathologically evaluated as benign.Conclusions Given the higher risk of malignancy associated with thyroid nodules in children compared to adults, surgical decision-making should incorporate both ultrasonographic risk features and cytological classification based on the Bethesda System. When multiple suspicious ultrasound findings are present, surgical intervention should be considered even in cases with benign or indeterminate cytology.
Keywords: thyroid nodule; children; papillary thyroid carcinoma